I'm here to kill you : The last mountain man and the taming of the West [large type] - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Smoke Jensen novel of the West., 2026)
Brutal night of the mountain man: Smoke Jensen helps a saloon owner defend her family and business against the ruthless rancher Silas Atwood and his army of killers. After a man guns down a greedy, overbearing rancher in self-defense, Smoke Jensen and his posse come to his defense when the rancher's goons aim to string him up.